Pengaruh Pemasaran Digital dan Online Customer Review Terhadap Keputusan Pembelian Pada Produk Skincare di E-Commerce Shopee (Literature Review Manajemen Pemasaran) - Shafwah, Allya Dina; Fauzi, Achmad; Caesar, Leo Andri Yulius; Octavia, Aurelia; Indrajaya, Bella Lorenza; Endraswari, Johana Iva; Yulia, Michely Noorma (Jurnal Ilmu Manajemen Terapan, 2024)
Relevant and previous research is one of the important factors in a scientific articleresearch. Relevant and previous research is useful to strengthen and reinforce the theory usedin research and help determine the relationship or influence that occurs between variables.This article reviews the factors that influence purchasing decisions, namely: digital marketingand online customer reviews. The purpose of writing this article is to build hypotheses ofinfluence between variables that will be used for future research. The results of this literaturereview article are: (1) Digital marketing affects purchasing decisions; (2) Online customerreviews affect purchasing decisions, and (3) Digital marketing and online customer reviewssimultaneously affect purchasing decisions.